PKM pelatihan komunikasi interpersonal bagi Guru BK di Kabupaten Pinrang - Muhammad Anas; Abdullah Sinring (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
The objectives of this activity are: 1) To find out about BK teacher's general description of basic counseling skills. 2) find out the extent of the ability of non-BK teachers to apply the basics of counseling skills. 3) find out the influence of basic counseling skills training in increasing the ability of BK services in schools ?. The interpersonal communication skills training took place for one day on June 21, 2019 at SMAN 4 Pinrang Building. Followed by 47 people from BK counseling teachers in Pinrang Regency. Presentation of material Interpersonal communication skills training began with the opening of the Chairperson of the PC Abkin Pinrang, and to the District Education Office of Pinrang. Presentation of basic skills counseling material went well, the participants present were very enthusiastic in the activity, these various participants gave feedback questions on each presentation of material provided by the resource persons basic counseling skills. On that day the participants were given an introduction to the service activities about the purpose of implementing PKM basic skills counseling for BK BK BK teachers in Pinrang district. Participants in basic counseling skills get an overview of the basic basic counseling and how to implement counseling skills. In addition to knowing the data on the results of understanding and knowledge through the practice of interpersonal communication skills on participants, the results of the questionnaire analysis test are free test and post test. the results of filling out the questionnaire had a significant effect on increasing participants' understanding and knowledge. The percentage of the results of the implementation of this activity we can describe are: from the analysis results there is a mean score of understanding of interpersonal communication skills before training that is 23.12 and the magnitude of the mean value after training is 63.06, so there are differences in score scores before and after narrative counseling training by 39.94, an increase in the average percentage score of Participants before and after interpersonal communication skills training is 60%. This increase shows a significant difference, in the understanding and knowledge of BK teachers in Pinrang district, and it has a positive contribution in improving the ability of BK teachers in schools, especially interpersonal communication skills